Developing strategic writers through genre instruction resources for grades 3-5 - Philippakos, Zoi A.; MacArthur, Charles A.; Coker, David L. Jr. (New York The Guilford Press, 2015)
"The Common Core State Standards (CCSS) identify three essential writing genres--narrative, persuasive, and informative. This highly practical guide offers a systematic approach to instruction in each genre, including ready-to-use lesson plans for grades 3-5. Grounded in research on strategy instruction and self-regulated learning, the book shows how to teach students explicit strategies for planning, drafting, evaluating, revising, editing, and publishing their writing. Sixty-four reproducible planning forms and student handouts are provided in a convenient large-size format; purchasers also get access to a Web page where they can download and print the reproducible materials. The Appendix contains a Study Guide to support professional learning"--Provided by publisher.
Machine generated contents note: 1. Writing Strategically: An Introduction to Genre-Based Strategy Instruction -- 2. Principles of Genre-Based Strategy Instruction -- 3. Making It Work: The Instructional Sequence and Organization of the Lessons -- 4. Story Writing -- 5. Persuasive Writing -- 6. Compare-Contrast Writing -- 7. How to Plan Your Own Genre-Based Strategy Instruction Lessons -- Appendix -- Study Guide.
Includes bibliographical references (pages 247-249) and index.
Keywords: Language arts (Elementary); Education -- Standards -- United States